Buried communities : Wordsworth and the bonds of mourning - Fosso, Kurt, 1958- (State University of New York Press, 2004)
"Kurt Fosso's Buried Communities analyzes the social relationship between mourning and community in William Wordsworth's writings from 1785 to 1814. Buried Communities situates Wordsworth as a reformist during a time of social and political crisis, for whom mourning promised to bind together his disaffected countrymen and disjointed world. With its sociological vantage and strong commitment to historical explanation, the book illuminates an important, previously unseen vista for understanding this Romantic poet's representations of death and grief and significantly reframes the cultural dynamics of the Romantic period in Britain."--BOOK JACKET.